MINAT BERWIRAUSAHA GENERASI Z DALAM BIDANG PENDIDIKAN: STUDI LITERATUR - Alda Mafrikha Fauziah; Ananda Suci Rahmania; Muhammad Tsaqolain Jaros; Ferida Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Rapid advancements in digital technology have transformed the landscape of education and the business world, providing significant opportunities for Generation Z (Gen Z) to become edupreneurs thanks to their creativity, adaptability, and technological proficiency. However, their interest in entrepreneurship does not arise spontaneously but is influenced by both internal and external factors. This study, conducted using a qualitative approach and a literature review, aims to analyze the entrepreneurial characteristics of Gen Z, identify the factors influencing their interest in entrepreneurship, and design strategies to foster that interest through education. Data collection was conducted by reviewing relevant academic documents, journal articles, and books. The findings of this study confirm that Gen Z has high entrepreneurial aspirations and a good level of digital literacy, even though they face challenges in the form of consumerist habits and a tendency to prefer instant gratification. Their interest in entrepreneurship in the field of education is influenced by four key factors: intrinsic motivation, self-efficacy (belief in one’s own abilities), support from the family environment, and the quality of the entrepreneurship education they receive. In conclusion, to optimize this potential, five integrated strategies are needed in the context of education: aligning the entrepreneurship curriculum, implementing project-based learning methods, making productive use of digital technology and social media, boosting motivation and self-confidence, and fostering a positive entrepreneurial climate in schools and universities. Through these strategies, educational institutions will not only produce graduates who are ready for the workforce but also foster a generation that is independent, innovative, and capable of creating their own job opportunities.